Aerobic Training Is Better Than Resistance Training on Cardiac Function and Autonomic Modulation in Female ob/ob Mice - Filipe Fernandes Stoyell-Conti; Filipe Fernandes Stoyell-Conti; Maria-Claudia Irigoyen; Michelle Sartori; Amanda Aparecida Ribeiro; Fernando dos Santos; Jacqueline Freire Machi; Jacqueline Freire Machi; Diego Mendrot Taboas Figueroa; Bruno Rodrigues; Kátia De Angelis; Kátia De Angelis (Frontiers in Physiology, 2019)
Objective: This study evaluated the effects of aerobic, resistance, and combined exercise training on cardiac function and autonomic modulation in female ob/ob mice.Methods: Four-week-old female wild type and obese (ob/ob) mice were divided into five groups (n = 8): control (WT), obese (OB) obese + aerobic training (OBA), obese + resistance training (OBR), and obese + combined training (OBC). The exercise training was performed on treadmill and/or ladder at 40–60% maximum test during 8 weeks. Cardiac function was measured using echo machine. Heart rate variability (HRV) was evaluated in the time and frequency domain.Results: OB group presented higher body weight gain (~600%), glycemia (~44%) and glucose intolerance (~150%), reduction of cardiac vagal modulation, evidenced by a lower RMMSD (~56%), total power and high frequency band, and a higher isovolumic relaxation time (IVRT) (~24%) in relation to the WT group. Aerobic and combined training led to a lower IVRT (OBA: ~14%; OBC: ~14%) and myocardial global index (OBA: ~37%; OBC: ~44%). The OBA group presented an increased in vagal indexes of HRV than the other ob/ob groups. A negative correlation was observed between the delta of aerobic exercise capacity and MPI (r = 0.45; p = 0.002) and exercise capacity and body weight gain (r = 0.39; p = 0.002).Conclusion: Only the obese females underwent to aerobic exercise training showed improvement in cardiac function and HRV. Moreover, the aerobic exercise capacity as well as a greater responsivity to aerobic exercise training is intimately associated with these improvements, reinforcing the importance of aerobic exercise training to this population.